EFEKTIVITAS MODEL PROBLEM BASED LEARNING UNTUK PENINGKATAN HASIL BELAJAR IPAS SISWA SEKOLAH DASAR - Sigit Arvianto; Nurhayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of elementary school students, which are influenced by the dominance of conventional teaching methods and limited active student participation. The purpose of this research was to examine the effect of implementing the Problem Based Learning (PBL) model on improving students’ learning outcomes in Integrated Science and Social Studies (IPAS). This study employed a quantitative approach with a pre-experimental design using a one-group pretest-posttest format. The participants consisted of 22 fourth-grade students at SD Muhammadiyah Brebes. Data were collected through pretest and posttest assessments administered before and after the implementation of the PBL model. The data were analyzed using normality testing, paired sample t-test, and N-Gain analysis with the assistance of SPSS software. The results revealed a significant difference between pretest and posttest scores, with a significance value of 0.000 (p < 0.05), indicating that the implementation of PBL had a significant effect on students’ learning outcomes. In addition, the average N-Gain score of 0.7168 was categorized as high, suggesting that the PBL model is effective in enhancing students’ conceptual understanding in IPAS. Therefore, Problem Based Learning has the potential to serve as an alternative instructional strategy to improve the quality of learning and promote active student engagement in the learning process.